PERANCANGAN DAN IMPLEMENTASI SISTEM INFORMASI DESA WISATA KANDRI BERBASIS WEB - Suprihadi Suprihadi; Agustinus Fritz Wijaya; Richard Gordon Mayopu (CCIT Journal, 2016)
Kandri is Gunungpati administrative area in the district, which is located in the city of Semarang in Central Java province which have Kreo Caves Nature Area. The tourist area has now been developed with the construction of dam Artificial Jatibarang which was completed in 2014. The reservoir has sunk acres of farmland, resulting in most of the Kandri citizens lose their livelihoods as farmers, and switch to the efforts in the field of tourism. Kandri rural communities in the development of a tourist village has set up a group called Pokdarwis tourism awareness in the form of a tourism cluster. The tourism cluster not yet have an information system that is capable of managing a data member, as well as a means of product promotion and online sales. This research aims to design a cluster of business information systems, and implement into web technology. System development method used is prototype models. The information system is implemented using the programming language PHP and CodeIgniter framework with a MySQL database. Results of this research is an e-commerce information system that features business profile information management, resource development and asset cluster members. These systems also use social plugins that like facebook as a marketing tool products. Thus, the information system can be used as an online store business clusters, media promotion, and data center can yield information about the development of the classification of business entities SME cluster members, so it can be used by cluster administrators and stakeholdesr in monitoring the business development of its members.